PANCASILA EDUCATION AND RELIGIOUS MODERATION - Dika Ayu Pramesti Dika Ayu Pramesti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
Indonesia as a country that has diversity certainly has its own challenges regarding its nation. Pancasila is present as an ideology, identity, the basis of the Indonesian state that must be understood by all citizens. However, in its development, various problems emerged that threatened the unity and integrity of the Indonesian nation. Like the emergence of radicalism movements in Indonesia. Therefore, it is important to make efforts to prevent the spread of radicalism in Indonesia. The purpose of this research is to provide an overview of the condition of the Indonesian nation and to provide an offer regarding efforts to prevent the spread of radicalism. This research is library research or literature review. The research method used is a qualitative method. The results of the research show that several efforts that can be made to prevent radicalism from developing in Indonesia are through Pancasila education and religious moderation. Both are in line with the ideals of the nation which expects unity and oneness in the midst of diversity.